Pediatric Flatfeet—A Disease Entity That Demands Greater Attention and Treatment - Bresnahan, Philip J.; Juanto, Mario A. (Frontiers in Pediatrics, 2020)
Pediatric flatfeet – a disease entity that demands greater attention and treatment. Abstract Background Pediatric flatfoot is a common deformity. Unfortunately, the common opinion has been that most children with this faulty foot structure will simply out-grow it, despite no radiographic evidence to support this claim. Every step on a deformed foot leads to excessive tissue strain and further joint damage. Many forms of conservative and surgical treatments have been offered. This study was aimed at investigating the effectiveness of non-surgical and surgical treatment options. Main Text A faulty-foot structure is the leading cause of many secondary orthopedic deformities. A wide range of treatments for pediatric flatfeet have been recommended from the “do-nothing” approach, observation, to irreversible reconstructive surgery. Most forms of conservative care lack evidence of osseous realignment and stability. A conservative surgical option of extra-osseous talotarsal joint stabilization provides patients an effective form of treatment without the complications associated with other irreversible surgical procedures. Conclusion Pediatric flatfeet should not be ignored or downplayed. The sooner effective treatment is prescribed, the less damage will occur to other parts of the body. When possible, a more conservative corrective procedure should be performed prior to irreversible, joint destructive options. Key Words: Pediatric Flatfeet, Hyperpronation, Pes planus, subtalar joint instability, Extra-osseous talotarsal stabilization,